American Like Me : Reflections on Life Between Cultures (Gallery Books, 2018)
Now, in American Like Me, America invites thirty-one of her friends, peers, and heroes to share their stories about life between cultures. We know them as actors, comedians, athletes, politicians, artists, and writers. However, they are also immigrants, children or grandchildren of immigrants, indigenous people, or people who otherwise grew up with deep and personal connections to more than one culture. Each of them struggled to establish a sense of self, find belonging, and feel seen. And they call themselves American enthusiastically, reluctantly, or not at all.